Recent Advances and Future Directions in Poultry Nutrition- An Overview - Belim, Saman Yusufkhan; Savsani, H.H.; Odedra, M.D.; Vaghamashi, D.G.; Kansagara, Y. G.; Kansagara, B.K.; Makwana, K.R. (Indian Journal of Animal Nutrition, 2021)
The poultry industry in India has made a remarkable growth and it is currently emerging as a sunrise sector. The worldwide consumption of poultry products such as meat plus eggs are currently high and tends to grow continuously as compared to other livestock products. So, it is important to know what were the recent advances that were made and what will be the future directions in poultry nutrition in a brief. Recent advances that have made includes defining nutrient requirements and nutrient composition, least cost feed formulations based on amino acid and energy, use of biotechnological products in poultry feeding as well as nano minerals supplementation. There are certain future directions like use of alternative raw material, use of phytogenic feed additives as alternative to antibiotic growth promoter, focus on gizzard development and gut health, use of next generation feed enzymes and in ovo nutrition are of prime importance.